Routine use of ultrasound imaging to diagnose skier’s thumb. Results from a first-aid orthopedic department in an Italian ski resort - Molinari, Marco; Portolano, Vincenzo; Pagliari, Micaela; Crespan, Beatrice; Giardini, Piero (Lo Scalpello - Journal, 2022)
Damage to the ulnar collateral ligament (UCL) of the thumb’s metacarpophalangeal joint (TMPJ) can result in severe functional impairment: correct diagnosis is critical to ensure the appropriate treatment to restore full TMPJ function. In an acute phase, clinical findings and X-rays alone are not reliable enough for a precise diagnosis: ultrasound scan (USS) may represent a fast, inexpensive and sensitive technique to improve the diagnosis of thumb trauma in emergency department. The purpose of this study is to assess if the introduction of the routine use of USS in clinical practice to evaluate thumb trauma could aid in diagnosis and treatment of this common injury. During eight winter seasons (2012-19), we dealt with 2553 injuries of the TMCJ at our emergency department. During the first period (2012-2015), the diagnosis of TMCJ injuries relied on clinical examination and X-rays; in the second study period (2016-2019) the diagnosis of all thumb traumas were based on clinical examination, radiographs, and ultrasound. Patients affected by type I and II lesions were conservatively treated by the application of a thumb spica plaster for three weeks, while in type III injuries for a period of one month. Type IV UCL lesions underwent surgery through a phalanx tunneling and anchor fixation technique followed by 5-weeks of immobilization in a thumb spica plaster cast. Both groups were followed up either clinically or as phone consultations for foreign patients. In the period 2012-2015, we classified 27% of TMPJ lesions as type I, 19% as type II, 15% as type III, and 27% as type IV lesions. The remaining 12% represented a fracture variant (type V). USS identified 30% type I, 21% type II, 18% type III, and 19% type IV lesions, the latter with a positive so called tadpole sign (14) (247 pts.); the remaining 12% of patients presented a fracture variant. During the first study period, the diagnosis of TMPJ injuries made exclusively by clinical examination and X-ray studies, lead to a high number of false positive type IV diagnoses that were not confirmed during surgery (13%). The introduction of USS imaging during the second period led to a detection of almost all (> 98%) type IV lesions intra-operatively, thereby avoiding unnecessary surgery, possible complications, rehabilitation, and recovery. Our work demonstrates that the routine use of USS imaging in the study of thumb UCL injuries improves the diagnostic sensitivity of clinical findings in a low cost, quick and feasible manner. USS can lead to a significant decrease in the number of misdiagnoses as previously demonstrated by other studies. USS is likely to improve patient collaboration and could potentially supplant stress-test radiography which can be painful and potentially risky in some patients.